Surgical Intervention for Two Patients Suffering from Pituitary Apoplexy Associated with Covid-19 - Yazbeck, Mohamad; Fadel, Elissa Abi; Berjaoui, Christin; Abadjian, Gerard; Akiki, Beatrice; Comair, Youssef (Archives of Clinical and Medical Case Reports, 2021)
Background: Pituitary apoplexy (PA), which is mainly associated with pituitary adenomas, is a very rare disease. PA imposes high risk of hemorrhages and infarction, which in most cases; emergent surgical intervention would be needed. Moreover, SARS-CoV-2 is a newly emergent viral infection, which has shown several neurological manifestations, including intracranial hemorrhages. Yet, a definitive correlation between PA and COVID-19 still needs further investigations. Observations: We report two cases of COVID-19 male patients, who presented with PA manifestations, mainly headache associated with ocular paresis and diplopia. Both patients underwent transsphenoidal resection of the sellar tumor, and both showed significant clinical improvement. Conclusion: Pituitary apoplexy has been linked to COVID- 19 as a post-infection complication, with surgery being a successful treatment.